2022
DOI: 10.3390/ijms232415937
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cytokines in Coronary Atherosclerotic Plaque: Current Therapeutic Approaches

Abstract: Coronary atherosclerosis is a chronic pathological process that involves inflammation together with endothelial dysfunction and lipoprotein dysregulation. Experimental studies during the past decades have established the role of inflammatory cytokines in coronary artery disease, namely interleukins (ILs), tumor necrosis factor (TNF)-α, interferon-γ, and chemokines. Moreover, their value as biomarkers in disease development and progression further enhance the validity of this interaction. Recently, cytokine-tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 243 publications
0
14
0
Order By: Relevance
“…The level of serum cytokines is often used to reflect the body’s inflammatory state and inflammatory response bias. 18 , 19 It has been shown that cardiovascular disease was closely related to cytokines. Several studies have uncovered an association between CAD and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The level of serum cytokines is often used to reflect the body’s inflammatory state and inflammatory response bias. 18 , 19 It has been shown that cardiovascular disease was closely related to cytokines. Several studies have uncovered an association between CAD and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory processes are associated with the initiation and progression of mental disorders ( Ben-Azu et al, 2022a ; Ben-Azu et al, 2023 ). Mental disorders may enhance the expression of pro-inflammatory cytokines, such as interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-ɑ), which are associated with endothelial dysfunction and metabolic alterations ( Vaccarino et al, 2018 ; Misiak et al, 2022 ; Tsioufis et al, 2022 ; Chen et al, 2023 ). Inflammation, vascular dysfunction, and metabolic abnormalities frequently contribute to the pathogenesis of heart diseases.…”
Section: The Relationships Between Heart Diseases and Mental Disordersmentioning
confidence: 99%
“…63 Undoubtedly, the adverse effects caused by higher dose will compromise its therapeutic benefits, therefore leading to the result that higher dose is inferior to lower dose in the therapeutic efficacy. Thus, based on the possible mechanisms of colchicine in exerting anti-inflammation, it is rational to extend the usage of colchicine from secondary prevention to primary prevention for cardiovascular diseases, especially low dose of colchicine 64 ; however, this hypothesis should be evaluated by future studies, such as an ongoing study registered on ClinicalTrials.gov. 65 Although our network meta-analysis suggested a significantly lower risk of recurrent MI in patients receiving low dose of colchicine and a numerically lower risk in cardioembolic stroke.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%